HER2 overexpression and amplification as a potential therapeutic target in colorectal cancer: analysis of 3256 patients enrolled in the QUASAR, FOCUS and PICCOLO colorectal cancer trials. Issue 4 (29th January 2016) - Richman, Susan D; Southward, Katie; Chambers, Philip; Cross, Debra; Barrett, Jennifer; Hemmings, Gemma; Taylor, Morag; Wood, Henry; Hutchins, Gordon; Foster, Joseph M; Oumie, Assa; Spink, Karen G; et al.
Abstract: HER2 overexpression/amplification is linked to trastuzumab response in breast/gastric cancers. One suggested anti‐EGFR resistance mechanism in colorectal cancer (CRC) is aberrant MEK–AKT pathway activation through HER2 up‐regulation. We assessed HER2‐amplification/overexpression in stage II–III and IV CRC patients, assessing relationships to KRAS/BRAF and outcome. Pathological material was obtained from 1914 patients in the QUASAR stage II–III trial and 1342 patients in stage IV trials (FOCUS and PICCOLO). Tissue microarrays were created for HER2 immunohistochemistry. HER2 ‐amplification was assessed using FISH and copy number variation. KRAS / BRAF mutation status was assessed by pyrosequencing. Progression‐free survival (PFS) and overall survival (OS) data were obtained for FOCUS/PICCOLO and recurrence and mortality for QUASAR; 29/1342 (2.2%) stage IV and 25/1914 (1.3%) stage II–III tumours showed HER2 protein overexpression. Of the HER2‐overexpressing cases, 27/28 (96.4%) stage IV tumours and 20/24 (83.3%) stage II–III tumours demonstrated HER2 amplification by FISH; 41/47 (87.2%) also showed copy number gains. HER2‐overexpression was associated with KRAS / BRAF wild‐type (WT) status at all stages: in 5.2% WT versus 1.0% mutated tumours ( p < 0.0001) in stage IV and 2.1% versus 0.2% in stage II–III tumours ( p = 0.01), respectively. HER2 was not associated with OS or PFS. At stage II–III, there was no significant correlation between HER2 overexpression and 5FU/FA response. A higher proportion of HER2‐overexpressing cases experienced recurrence, but the difference was not significant. HER2‐amplification/overexpression is identifiable by immunohistochemistry, occurring infrequently in stage II–III CRC, rising in stage IV and further in KRAS / BRAF WT tumours. The value of HER2‐targeted therapy in patients with HER2 ‐amplified CRC must be tested in a clinical trial. © 2015 The Authors. Journal of Pathology published by John Wiley & Sons Ltd on behalf of Pathological Society of Great Britain and Ireland.